2020
DOI: 10.3390/nu12010131
|View full text |Cite
|
Sign up to set email alerts
|

The Mediterranean Diet is Associated with an Improved Quality of Life in Adults with Type 1 Diabetes

Abstract: This study aimed to assess the potential association between dietary patterns (i.e., the Mediterranean Diet (MedDiet) and healthy eating) and patient-reported quality of life (QoL) and treatment satisfaction (TS) in adults with type 1 diabetes (T1D). A food frequency questionnaire, the Audit of Diabetes-Dependent Quality of Life (ADDQoL-19), and the Diabetes Treatment Satisfaction Questionnaire-status version (DTSQ-s) were administered via personal interviews to 258 participants with T1D. Multivariable analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…To date, numerous scientific studies have shown that the MD protects from cardiovascular diseases 54–59 and certain types of cancer, 60–63 increases longevity, enables healthy aging 64‐70 and improves mental health and quality of life. Immunity boosting by adherence to an MD lifestyle is also reported by several authors, 71,72 as well as the diet's positive effects on metabolic syndrome and obesity, 73–78 diabetes 56,79–81 and hypertension. 82,83 .…”
Section: Health Benefits Of Mediterranean Dietmentioning
confidence: 60%
“…To date, numerous scientific studies have shown that the MD protects from cardiovascular diseases 54–59 and certain types of cancer, 60–63 increases longevity, enables healthy aging 64‐70 and improves mental health and quality of life. Immunity boosting by adherence to an MD lifestyle is also reported by several authors, 71,72 as well as the diet's positive effects on metabolic syndrome and obesity, 73–78 diabetes 56,79–81 and hypertension. 82,83 .…”
Section: Health Benefits Of Mediterranean Dietmentioning
confidence: 60%
“…Not relevant to the topic examined studies, studies including population <18 years old, studies in which validated tool for assessment of MD were not used and in which the level of adherence was not clearly described were excluded. Overall, 58 studies were characterized as acceptable for the systematic review [ 39 , 40 , 43 , 44 , 45 , 46 , 47 , 49 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ,…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were characterized as unsatisfactory due to their ratings (2–4 stars) [ 43 , 67 , 75 , 80 , 107 ], whereas for 17 studies the quality was only satisfactory (5–6 stars) [ 39 , 49 , 61 , 63 , 71 , 86 , 92 , 93 , 94 , 96 , 97 , 100 , 104 , 105 ]. The majority of the included studies ( n = 28) [ 40 , 44 , 45 , 47 , 58 , 59 , 60 , 62 , 65 , 68 , 69 , 70 , 72 , 74 , 76 , 77 , 79 , 81 , 82 , 83 , 84 , 85 , 87 , 88 , 95 , 101 , 103 , 106 ] were good quality studies (7–8 stars), and eight studies were at the top of quality studies scoring 9 stars [ 46 , 64 , 66 ...…”
Section: Resultsmentioning
confidence: 99%
“…There are no studies specifically investigating the effects of MD on glycaemic control in adults with type 1 diabetes, although a cross‐sectional study in Canada reported that a higher MD score was associated with a more favourable cardiometabolic profile 43 . One small, short‐term study comparing the effects of MD with low fat diets in adults with both type 1 diabetes and the metabolic syndrome reported some beneficial effects for both interventions with no significant difference between the groups, 44 and one qualitative study reported improved quality of life in those adopting MD 45 . However, a recent cross‐sectional study from Germany reported that closer adherence to MD was not associated with cognitive performance in people with type 1 diabetes 40 …”
Section: Type 1 Diabetesmentioning
confidence: 99%